2020
DOI: 10.3390/separations7040054
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS Phytochemical Screening, In Vitro Antioxidant, Antimicrobial and Anticancer Activity of Microalgae Nannochloropsis oculata Extract

Abstract: Nowadays, marine microalgae are recognized to be a considerably novel and rich origin of bioactive moieties utilized in the sectors of nutraceuticals and pharmaceuticals. In the present study, Nannochloropsis oculata extract (AME) was associated with a wide variety of pharmacological studies such as in vitro antioxidant, antibacterial, and antifungal and anticancer activity (MDA-MB-231) in cancer cells through in vitro models. In the study, the chemical composition and structure of the bioactive compounds foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…I. galbana clone Tahiti with a total phenol content of 17.798 mg GAE g-1 (Gallic Acid Equivalent), showed the highest antioxidant activity with 61.64% of inhibition at 50 ppm, followed by D. salina with 58.45% and T. chuii with 52.58% of inhibition. A study by Wali et al [ 28 ] showed that Nannochloropsis oculata , contains a higher amount of polyphenol and exhibited in-vitro ROS scavenging activity, with an IC50 of 52.10 ± 0.85 µg/L.…”
Section: Ros (Reactive Oxygen Species) and Antioxidantsmentioning
confidence: 99%
“…I. galbana clone Tahiti with a total phenol content of 17.798 mg GAE g-1 (Gallic Acid Equivalent), showed the highest antioxidant activity with 61.64% of inhibition at 50 ppm, followed by D. salina with 58.45% and T. chuii with 52.58% of inhibition. A study by Wali et al [ 28 ] showed that Nannochloropsis oculata , contains a higher amount of polyphenol and exhibited in-vitro ROS scavenging activity, with an IC50 of 52.10 ± 0.85 µg/L.…”
Section: Ros (Reactive Oxygen Species) and Antioxidantsmentioning
confidence: 99%
“…H1 and H4 are proteinaceous halocins of roughly 30–40 kDa [ 109 ], whereas C8, H6, H7, R1, U1, and S8 are microhalocins which are smaller than 10kDa. Microhalocins are more vigorous than proteinaceous halocins since they are resistant to varying temperature, salinity, exposure to organic solvents, acids, and bases [ 109 ]. Halocins have wide-ranging activity against haloarchaea and members of the family Halobacteriaceae [ 110 ].…”
Section: Archaeamentioning
confidence: 99%
“…Extracts of Chlorella vulgaris and Chlorella minutissima showed strong antifungal activity against Aspergillus niger and Fusarium oxysporum [67]. Recently, antifungal activity was reported in extracts of Nannochloropsis oculata against Candida albicans, where the bioactive compounds were terpenoids, carotenoids, polyphenols, and fatty acids [68].…”
Section: Antifungal Activitymentioning
confidence: 99%